Evaluation of a method for the simultaneous quantification of N‐nitrosamines in water samples based on stir bar sorptive extraction combined with high‐performance liquid chromatography and diode array detection. Issue 9 (14th April 2015) - Talebpour, Zahra; Rostami, Simindokht; Rezadoost, Hassan
<x xml:space="preserve">Abstract</x> A simple, sensitive, and reliable procedure based on stir bar sorptive extraction coupled with high‐performance liquid chromatography was applied to simultaneously extract and determine three semipolar nitrosamines including N‐nitrosodibutylamine, N‐nitrosodiphenylamine, and N‐nitrosodicyclohexylamine. To achieve the optimum conditions, the effective parameters on the extraction efficiency including desorption solvent and time, ionic strength of sample, extraction time, and sample volume were systematically investigated. The optimized extraction procedure was carried out by stir bars coated with polydimethylsiloxane. Under optimum extraction conditions, the performance of the proposed method was studied. The linear dynamic range was obtained in the range of 0.95–1000 ng/mL (r = 0.9995), 0.26–1000 ng/mL (r = 0.9988) and both 0.32–100 ng/mL (r = 0.9999) and 100–1000 ng/mL (r = 0.9998) with limits of detection of 0.28, 0.08, and 0.09 ng/mL for N‐nitrosodibutylamine, N‐nitrosodiphenylamine, and N‐nitrosodicyclohexylamine, respectively. The average recoveries were obtained >81%, and the reproducibility of the proposed method presented as intra‐ and interday precision were also found with a relative standard deviation <6%. Finally, the proposed method was successfully applied to the determination of trace amounts of selected nitrosamines in various water and wastewater samples and the obtained results were confirmed using mass spectrometry.